2003
DOI: 10.1034/j.1398-9995.2003.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking in pregnancy alters neonatal cytokine responses

Abstract: These findings indicate that maternal cigarette smoking can modify aspects of fetal immune function and highlight the need for further studies in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
1
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(145 citation statements)
references
References 45 publications
(52 reference statements)
4
135
1
5
Order By: Relevance
“…While smokers are notoriously susceptible to infections and exhibit diminished cell-mediated immunity [Sopori 2002] they also present with higher levels of inflammatory diseases [Kitamura and Kasai 2007], autoantibody production, leukoctyosis, and increased risk of rheumatoid arthritis, systemic lupus erythematosus and Graves' disease [Costenbader and Karlson 2006;Klareskog et al 2007;Vestergaard et al 2002]. Maternal smoking during pregnancy is associated with higher cord blood IgE (which does not cross the placenta) [Magnusson 1986], stronger neonatal lymphoproliferation [Noakes et al 2003], and increased rates of asthma and allergy in children [Gilliland et al 2001;Magnusson 1986]. In mice, cigarette smoke stimulated oligoclonal expansion of T lymphocytes, leading to a persistent, adaptive T cell immune response [Motz et al 2008] and in utero exposure resulted in elevated levels of circulating white blood cells in the offspring [Ng and Zelikoff 2008].…”
Section: Cigarette Smoke Pahs Ahr and The Immune Systemmentioning
confidence: 99%
“…While smokers are notoriously susceptible to infections and exhibit diminished cell-mediated immunity [Sopori 2002] they also present with higher levels of inflammatory diseases [Kitamura and Kasai 2007], autoantibody production, leukoctyosis, and increased risk of rheumatoid arthritis, systemic lupus erythematosus and Graves' disease [Costenbader and Karlson 2006;Klareskog et al 2007;Vestergaard et al 2002]. Maternal smoking during pregnancy is associated with higher cord blood IgE (which does not cross the placenta) [Magnusson 1986], stronger neonatal lymphoproliferation [Noakes et al 2003], and increased rates of asthma and allergy in children [Gilliland et al 2001;Magnusson 1986]. In mice, cigarette smoke stimulated oligoclonal expansion of T lymphocytes, leading to a persistent, adaptive T cell immune response [Motz et al 2008] and in utero exposure resulted in elevated levels of circulating white blood cells in the offspring [Ng and Zelikoff 2008].…”
Section: Cigarette Smoke Pahs Ahr and The Immune Systemmentioning
confidence: 99%
“…12 Mothers who smoked while pregnant gave birth to children with a greater risk of wheezing and asthma, and it was found that they had elevated IgE and IL-13 levels, but low IL-4 and IFN-γ levels, in cord blood, reduced airway caliber and reduced pulmonary function. [13][14][15] During the perinatal period, exclusive breastfeeding for the first 4 months of life may be a protective factor against wheezing; other studies have not however confirmed this hypothesis. 16,17 Respiratory viruses, such as syncytial respiratory virus, rhinovirus, metapneumovirus, parainfluenza type 3 and influenza are associated with increased risk of wheezing among preschool children.…”
Section: Epidemiology and Factors Associated With Wheezing In Preschomentioning
confidence: 89%
“…19 Induce cambios en el crecimiento pulmonar, hiperreactividad de las vías respiratorias, deterioro de la adaptación inmune a los patógenos virales, disminución del desarrollo del sistema inmune pulmonar y cambios inmunológicos que favorecen el desarrollo de la enfermedad alérgica. 20 Además, la inducción de estrés oxidativo y las modificaciones en la colonización bacteriana de las mucosas provocan mayor penetración de alérgenos. 21 La exposición posnatal inmediata se asocia con sibilancias en lactantes y aumento de la prevalencia de asma, independientemente del efecto de la exposición durante la gestación.…”
Section: Humo Del Tabacounclassified